Preoperative NRI outperforms other time points in predicting prognosis of ESCC with neoadjuvant therapy - Tang, Xue; Yang, Mei (Frontiers in Nutrition, 2025)
BackgroundEarly studies reported that the nutritional risk index (NRI) is a prognostic factor in patients with various malignant tumors. Our study aims to demonstrate the prognostic role of the NRI by assessing the longitudinal clinical data of patients with esophageal squamous cell carcinoma (ESCC) who had undergone neoadjuvant therapy followed by esophagectomy.Materials and methodsOur study retrospectively investigated 319 ESCC patients who had been treated with neoadjuvant therapy before esophagectomy at West China Hospital, Sichuan University, between August 2016 and August 2021. The NRI was calculated based on the height, weight, and albumin levels of ESCC patients at three time points during the entire treatment course: before treatment, before esophagectomy, and post-esophagectomy.ResultsA total of 319 patients with ESCC were included in the study. Logistic regression showed that ESCC patients with a low preoperative NRI had a higher postoperative complication rate than those with a high preoperative NRI (odds ratio [OR] = 2.324, 1.318–4.095, p = 0.004). The timing of malnutrition that affected survival was the preoperative NRI score. According to the multivariate analysis results, the preoperative NRI, rather than the pretreatment NRI or postoperative NRI, was an independent prognostic factor for overall survival (OS) (hazard ratio [HR] = 2.005, 1.070–3.760, p = 0.030) and disease-free survival (DFS) (HR = 1.736, 1.086–2.775, p = 0.021) in patients with ESCC.ConclusionIn patients with ESCC who underwent neoadjuvant therapy followed by esophagectomy, preoperative NRI might predict postoperative complications and survival outcomes of patients. Further clinical investigations are needed to determine the prognostic value of the NRI.